A Proteome-Level Investigation Into Plasmodiophora brassicae Resistance in Brassica napus Canola - Adhikary, Dinesh; Mehta, Devang; Uhrig, R. Glen; Rahman, Habibur; Kav, Nat N. V. (Frontiers in Plant Science, 2022)
Clubroot of Brassicaceae, an economically important soil borne disease, is caused by Plasmodiophora brassicae Woronin, an obligate, biotrophic protist. This disease poses a serious threat to canola and related crops in Canada and around the globe causing significant losses. The pathogen is continuously evolving and new pathotypes are emerging, which necessitates the development of novel resistant canola cultivars to manage the disease. Proteins play a crucial role in many biological functions and the identification of differentially abundant proteins (DAP) using proteomics is a suitable approach to understand plant–pathogen interactions to assist in the development of gene specific markers for developing clubroot resistant (CR) cultivars. In this study, P. brassicae pathotype 3 (P3H) was used to challenge CR and clubroot susceptible (CS) canola lines. Root samples were collected at three distinct stages of pathogenesis, 7−, 14−, and 21-days post inoculation (DPI), protein samples were isolated, digested with trypsin and subjected to liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis. A total of 937 proteins demonstrated a significant (q-value < 0.05) change in abundance in at least in one of the time points when compared between control and inoculated CR-parent, CR-progeny, CS-parent, CS-progeny and 784 proteins were significantly (q < 0.05) changed in abundance in at least in one of the time points when compared between the inoculated- CR and CS root proteomes of parent and progeny across the three time points tested. Functional annotation of differentially abundant proteins (DAPs) revealed several proteins related to calcium dependent signaling pathways. In addition, proteins related to reactive oxygen species (ROS) biochemistry, dehydrins, lignin, thaumatin, and phytohormones were identified. Among the DAPs, 73 putative proteins orthologous to CR proteins and quantitative trait loci (QTL) associated with eight CR loci in different chromosomes including chromosomes A3 and A8 were identified. Proteins including BnaA02T0335400WE, BnaA03T0374600WE, BnaA03T0262200WE, and BnaA03T0464700WE are orthologous to identified CR loci with possible roles in mediating clubroot responses. In conclusion, these results have contributed to an improved understanding of the mechanisms involved in mediating response to P. brassicae in canola at the protein level.